Development of the hybrid weight assessment system for multiple quality attributes - Sopadang A. (2014)
When designing a product or process, a design engineer is often faced with a number of quality attributes and hence prioritizing the quality attributes is an inevitable task. Development of an adequate weight assessment system for multiple attributes in the early stage of design is crucial, since the choice of paths to quality enhancement depends heavily upon the type of weight assessment system used. Although several weight assessment methods are available in the literature, there is room for improvement. Most weight assessment methods reported in the research community have been developed from the perspective of either customers or a design engineer. This article proposes a hybrid weight-assessment system by combining the perspectives of both parties, the customer and a design engineer, in such a way that uncertainty of human perceptions can be modeled using the concepts of fuzzy sets and Monte Carlo simulation. A model is presented and a numerical example is discussed.